Addressing negative spillover effects of overcrowding in Malaysian prisons: can Islamic financial institutions play a role? - Misman, Siti Nursyawani; Mohd Salimin, Mohd Ariff; Farjan Ali, Rahimah; Adnan, Ieman Huda; Kassim, Salina; Syed Azman, Syed Marwan Mujahid (Springer, 2023)
Over the years, the number of Malaysian prisoners continues to rise, resulting in overcrowding at prisons and further exposing the prisoners to various health and mental issues. Currently, it is the sole responsibility of the government to absorb the costs of maintaining the prisons, including maintenance and operating costs related to prisoners, currently estimated at around RM511 million. However, from the economic perspective, prison comprises abundant human capital resources, operating in restricted environments with high-level security measures. These resources have remained idle and are not being fully utilized for the generation of economic activities. Harnessing the full potential of the labor resources available in prisons will bring significant impact on the country’s economy in terms of cost reduction and increment in goods and service production. In this regard, the Islamic financial institutions (IFIs) have a potential role to play in addressing these issues, with the possibility that the IFIs provide financial resources and strengthen engagement with the prison department through innovative financing models towards the financial sustainability of the prisons. This study intends to conceptualize the role of IFIs in contributing towards developing the potentiality of prisoners as a productive economic resource and preparing them with financial independence upon their release from prison.